Influence of drying temperature on dietary fibre, rehydration properties, texture and microstructure of Cape gooseberry (Physalis peruviana L.) - Vega Gálvez, Antonio (2015)
The effects of air drying temperature on dietary fibre, texture and microstructure of the Cape gooseberry fruits during convective dehydration in the range of 50–90 ºC were investigated. The ratio of insoluble dietary fibre to soluble dietary fibre was higher than 7:1 for all dehydrated samples. At 50 ºC tissue structure damage was evidenced leading to the maximum water holding capacity (47.4 ± 2.8 g retained water/100 g water) and the lowest rehydration ratio (1.15 ± 0.06 g absorbed water/g d.m.). Texture analysis showed effects of drying temperatures on TPA parameters. Changes in microstructure tissue were also observed at the studied drying temperatures. Hot air drying technology leads not only to fruit preservation but also increases and adds value to Cape gooseberry, an asset to develop new functional products.